Assessing the longer-term impact of emergency food aid in Bangladesh, Ethiopia, and Malawi - Gilligan, Daniel O.; Hoddinott, John F.; Quisumbing, Agnes R.; Sharma, Manohar (International Food Policy Research Institute, 2005)
...IFPRI examined the effectiveness of community-based targeting following three recent emergencies: the 1998 floods in Bangladesh; the 2002 drought in Ethiopia; and the 2001-02 failed maize harvest in Malawi. All three cases show limited long-term impact in the aggregate from either food for- work or free food distribution, although positive impacts were found for some groups of recipients in all three studies. The sparse average impacts appear to be related to quantity, timing, and targeting. Households received only small amounts of food aid, when compared with their total consumption. In addition, some of the transfers arrived months after the crisis began. In many instances, they were not regularly available or sustained for more than a season. And targeting was in many cases inconsistent or ambiguous as to whether to focus on the poorest or those most affected by crisis.